Typifications and nomenclatural notes on Indian Myrtaceae - Byng, James; Wilson, Peter; Snow, Neil (Phytotaxa, 2015)
We discuss typification and present other nomenclatural notes for 44 taxa of Indian Myrtaceae. Lectotypes are designated for 28 species plus 6 synonyms in Syzygium and 6 species in Eugenia. A new combination, Syzygium coarctatum, and new synonyms of Syzygium bifarium and Syzygium stocksii are also recognised.